United States’ Political Rights Values: Critiques of Human Rights Violations Towards Hispanic Americans - Purwitasari, Artie Indah (Departemen Sosiologi Universitas Gadjah Mada, 2024)
This study examines the ongoing violations of political rights experienced by Hispanic Americans, despite the United States established democratic principles. It examines the impact of globalization on human rights issues, leading to the